PENGEMBANGAN SKALA REVISED PRENATAL DISTRESS QUESTIONNAIRE (NuPDQ) VERSI BAHASA INDONESIA - Justinus Budi Santoso (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2018)
The impacts of maternal mental health to the unborn child has not been researched as vastly as the impacts of physical health. One of the parameter of mental health during pregnancy is pregnancy specific distress (PSD). PSD can directly and indirectly affect the physical and mental aspects of a child, both during the pregnancy and after birth. There are several PSD risk factors relevant in Indonesia, namely young maternal age, economic pressure during pregnancy, and unwanted pregnancies. NuPDQ is a measure of PSD which have been translated to Indonesian language. The validity and reliability of the Indonesian version of NuPDQ is investigated here as part of its adaptational process. The results shown that 5 of 17 items have low (< 0.3) corrected item-total correlation with the total score, with two items having negative correlation coefficients. However, as a whole the NuPDQ still possessed an acceptable reliability (0.736). Considering the adequate reliability, the necessity to include various possible stressors in the instrument, and the small number of items, we suggest that the items with low corrected item-total correlations may still be included in relevant contexts. Further research with more heterogenous sample is necessary, especially in populations with high vulnerability to PSD. Further research is also needed to find the factor structure of the NuPDQ in Indonesia.